Biography of Prof. Dr. Albert Eckstein and His Studies in Türkiye - Ada, Turhan (AVES, 2025)
Objective: The aim of the article is to contribute to the international academic literature within the scope of Web of Science with a comprehensive article that complies with academic criteria on Prof. Eckstein and his studies in T & uuml;rkiye. Materials and Methods: First, this study scans all the literature on the subject and found the necessary books and articles. It uses Prof. Baskan's archive for the photographs. We found the work of Dr. Nuriye Peker with the help of Prof. Akar. The article covers Prof. Eckstein's life and focuses on the period in T & uuml;rkiye. Results: During the 1930s, a group of German medical doctors, led by German-Jewish pediatrician Prof. Eckstein, migrated to T & uuml;rkiye. Prof. Eckstein initiated scientific research on children's health and healthcare in remote Anatolian regions in 1937. This approach had a profound impact on the development of healthcare systems for large population segments in developing nations such as T & uuml;rkiye at that time. Prof. Eckstein and his assistants like Dr. Demira & gbreve;, Dr. Do & gbreve;ramac & imath;, and Dr. Cura are regarded as the pioneers of modern Turkish healthcare and health sciences. Conclusion: Prof. Eckstein excelled as a clinician, educator, and researcher, specializing in infectious diseases, disorders of the central nervous system, the biology of premature and newborn infants, and preventive pediatric care. His work in T & uuml;rkiye transformed pediatric practice and education by introducing Western medical knowledge and techniques. Eckstein's achievements include groundbreaking treatments for noma, an oral mucosa infection caused by Borrelia, and malaria.
Keywords: Albert Eckstein; history of medicine; history of pediatrics; Pediatrics